The smugglers - Lawrence, Iain, 1955- (New York : Dell, 2000)
In eighteenth-century England, after his father buys a schooner called the Dragon, sixteen-year-old John sets out to sail it from Kent to London and becomes involved in a dangerous smuggling scheme.
"A Yearling book.".
Companion to: The wreckers.
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
4.2
Keywords: Adventure and adventurers -- Fiction; Historical fiction; Ships -- Fiction; Smuggling -- Fiction; Adventure fiction; Historical fiction; Ships -- Fiction; Smuggling -- Fiction; England -- Fiction; England -- Fiction